SERS-active Metal-dielectric Nanostructures Integrated in Microfluidic Devices for Ultra-sensitive Label-free miRNA Detection. (2017) - Chiadò, A.; Novara, C.; Lamberti, A.; Geobaldo, F.; Giorgis, F.; Rivolo, P.
Abstract: In this work, silver decorated porous silicon membranes integrated in a polydimethylsiloxane multi-chamber microfluidic chip were functionalized with DNA-probes and used for the detection of miRNA by Surface-enhanced Raman Scattering analysis. An innovative biological protocol has been designed: the probe was divided in two short pieces that interact before and after the miRNA incubation. The optofluidic biosensor was applied for the label-free detection of miRNA sequences at in vivo concentrations.